Determining the Birth Weight of Creole and MEVEZUG Lambs Based on Sex and Type of Calving at Cd. Altamirano, Guerrero, Mexico - Martínez , Esteban Julián Mireles; Catalán , Adiel Robles; Rodríguez , Arelis Hernández; Galeana , José Alonso; Segura , Isidro Gutiérrez; Almazán , Ma. Trinidad Valencia; Huerta , Rosendo Cuicas (Newest Updates in Agriculture and Veterinary Science Vol. 3, 2023)
The present chapter aims to determine the birth weight of Creole and MEVEZUG lambs according to sex and type of calving. The records of the former correspond to the years 2006 to 2010, the later from 2010 to 2019 and 2020 to 2022. 1 516 records of data from an ovine herd composed averagely of 110 heads of sheep were analyzed. The sheep of the first years were of various colors as a result of crossbreeding among the Pelibuey, Black Belly, Dorper, and Katahdin breeds, whereas those of the later years were of pure color (light brown and tobacco brown) produced from the selection of the inbred cross of the first period herd. The feeding of sheep throughout the study period was based on grazing native meadows and irrigated areas during the dry season, when forage availability was lowest. Each animal received 100 grams of corn grain. The gathered data were subjected to analysis of variance, and the means were compared using the Tukey and Duncan test (P <0.05) and the statistical software infoStat. Average of male weighed was 2.96 kg with (P <0.0001) and 2.67 kg for females compared to MEVEZUG being 2.65 kg for males and 2.59 kg for females (P> 0.2819). In relation to the type of delivery, the values were 3.23, 2.69, 2.13 and 1.95 kg (P <0.0001) for single, double, triple and quadruple deliveries, respectively for Creoles and 2.98, 2.39 and 1.97 kg (P < 0.0001) for singles, doubles and triples, respectively for MEVEZUG lambs. It is determined that the Creoles had heavier male and female lambs than the MEVEZUG, and that in recent years, the MEVEZUG lambs had seen weight gain at birth.